Exploring hemorrhagic shock as a complication of negative pressure wound therapy in the treatment of lumbar spine infection: a case study and literature review - Ge Zhang; Junlin Pan; Shiyong Wan; Zhengqi Chang (Frontiers in Medicine)
Lumbar infectious diseases are serious debilitating conditions, and their treatment poses significant challenges. With the advancement of minimally invasive spinal techniques, negative pressure wound therapy (NPWT) has been widely recognized as an effective method for preventing and treating infected wounds. However, studies specifically focusing on hemorrhagic shock as a complication of NPWT in lumbar spine infections are limited. Here, we present a case of hemorrhagic shock as a postoperative complication of Brucella infection in the lumbar spine, and summarize the management of postoperative complications of lumbar infectious diseases treated with NPWT.